ANALISIS PENGARUH FAKTOR-FAKTOR SOSIAL EKONOMI TERHADAP CURAHAN WAKTU KERJA WANITA TANI KOPI ROBUSTA DI KECAMATAN JUMO KABUPATEN TEMANGGUNG - Nico Bimo Laksono; Bambang Trisetyo Eddy; Dyah Mardiningsih (Universitas Tadulako, 2018)
The purpose of this research was to determine the allocation of women workingtime on Robusta coffee farming during one harvest season and to analyze the influence of socio-economic factors such as age, education level, number of dependent family, income, planted land area, and farming experience on female farmers’ workingtime ofRobusta coffeein Jumosub district of Temanggung Regency. The research was conducted in December 2017 until January 2018. The respondents in this research were female farmers of Robusta coffee in Jumosubdistrict. The research method used survey and Quota Sampling technique to select 94 female farmer respondents.. Data analysis using multiple regression test with socio-economic factors as X variables, and women working time as Y variable. The results showed that all factors of production simultaneously had a significant effect on the women workingtime. Whereas the age, education level,number of dependent family, income, and planted land area partially had no significant influence on the women working time. It indicates that the Robusta coffee cultivation needs to reach a maximum working time to increase its productivity.